PENGEMBANGAN MEDIA GAME SCRATCH PADA PEMBELAJARAN IPA KELAS V MATERI ALAT PERNAPASAN PADA HEWAN - Putri Mulanisya Ayu Wardani; Erwin Putera Permana; Dhian Dwi Nur Wenda (STKIP PGRI Situbondo, 2022)
This research was motivated by the results of observations at SDN Mrican 1 class V science subjects on respiratory equipment in animals which showed that 60% of fifth grade students still had difficulty understanding the material. One of the reasons is that teachers tend to use existing media so that students are less enthusiastic in participating in learning. To overcome this problem, it is necessary to develop innovative learning media according to the material. This research is a Research and Development (R&D) research using the ADDIE development model. This development model has 5 stages, namely: Analysis (Analysis), Design (Design), Develompent (Development), Implementation (Implementation), Evaluation (Evaluation). The data collection instrument in this study used a questionnaire and a test. Questionnaires are used to determine the assessment given by media experts, material experts, classroom teachers to the developed media. While the test is used to measure the initial ability and final ability of students after using the media that has been developed. The results of this study are Game Scratch media is declared valid based on the results of expert validation and the material obtained is 88% and 89% is included in the very valid category. While the practicality questionnaire given by the teacher obtained 92% results categorized as very practical. In a limited trial, the result was 87.5%, so it was categorized as very effective.Based on the conclusions of this study, it is stated that the development of this media can help teachers to create a pleasant learning atmosphere and can arouse students' enthusiasm in participating in learning